PENGARUH ASIMETRI INFORMASI DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN PROPERTI YANG TERDAFTAR DI BEI - Lubis, Henny Zurika; Pratiwi, Dinda (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2020, 2021)
This research was conducted with the aim to test and analyze the effect of information asymmetry and company size on earnings management on property companies listed on the Indonesia Stock Exchange. The population in this study are all property companies listed on the Indonesia Stock Exchange while the samples that meet the criteria for sampling of observations made for five years and as many as seven property companies listed on the Indonesia Stock Exchange. This research approach uses associative research. Data collection techniques in this study using documentation techniques. and the analysis technique used is multiple linear regression analysis, hypothesis testing and coefficient of determination. The results showed that the independent variables in this study did not influence simultaneously on earnings management and testing partially proved the information asymmetry variable and company size had no effect and no significant effect on earnings management on property companies listed on the Indonesia Stock Exchange.